MaCDSP32 From Mulberry Enhances Resilience Post-drought by Regulating Antioxidant Activity and the Osmotic Content in Transgenic Tobacco - Sun, Hongmei; Zhao, Wenrui; Liu, Hui; Su, Chao; Qian, Yonghua; Jiao, Feng (Frontiers in Plant Science, 2020)
Desiccation tolerance is a complex phenomenon that depends on the regulated expression of numerous genes during dehydration and subsequent rehydration. Our previous study identified chloroplast drought-induced stress protein (MaCDSP32), a thioredoxin (Trx) that is upregulated under drought conditions in mulberry and is likely to confer additional drought tolerance to transgenic plants. Mulberry is an ecologically and economically important perennial woody plant that is widely used in the construction of forests to combat desertification. However, its stress tolerance physiology is not well understood. In this study, the functions of MaCDSP32 were investigated. The expression of MaCDSP32 exhibited a circadian rhythm and was induced by mild and severe water deficits. Under abiotic stress, MaCDSP32-overexpressing plants exhibited increased stress sensitivity with lower water retention capacity and more severe lipid peroxidation than the wild-type (WT) plants. Furthermore, the activity of superoxide dismutase (SOD), the contents of proline and soluble sugars and the expression of transcription factors were lower in the MaCDSP32-overexpressing plants than in the WT plants. However, the MaCDSP32-overexpressing lines exihited stronger recovery capability after rewatering post-drought. Moreover, the SOD enzyme activity, proline content, and soluble sugar content were higher in the transgenic plants after rewatering than in the WT plants. The production of superoxides (H2O2 and O2-) was significantly lower in the transgenic plants than in the WT plants. Under abiotic stress, the MaCDSP32-overexpressing lines showed increased post-drought recovery, improved seed germination and better seedling growth, and all of these effects were regulated by a positive redox reaction involving MaCDSP32. In summary, this study indicated that MaCDSP32 from mulberry mainly regulates reactive oxygen species (ROS) homeostasis by controlling SOD enzyme activity and the proline and soluble sugar concentrations, and these effects affect the stress response during seed germination and plant growth. Overall, MaCDSP32 exerts pleiotropic effects on the stress response and stress recovery in plants.